Faktor-Faktor Yang Berhubungan Dengan Kepuasan Pasien Pada Pelayanan Kesehatan Di UPT Puskesmas Sukaramai Kota Medan Tahun 2024 - Lyenta Simanullang; Mido Ester J Sitorus; Johansen Hutajulu; Manurung, Kesaktian; Dewi Mustikani Saragih; Rahmat Alyakin Dachi (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
Patient satisfaction is heavily influenced by the quality of services provided by healthcare centers (Puskesmas). The World Health Organization (WHO) states that good healthcare services are those that are effective, safe, and of high quality for those in need. This study aims to identify the factors associated with patient satisfaction regarding healthcare services at Puskesmas Sukaramai in 2024. The research is a quantitatfve study with a cross-sectional design, conducted in the operational area of Puskesmas Sukaramai, Medau City, from November 2023 to July 2024. The study population includes all patients visiting the Puskesmas, totaling 619 per month. The sample size was determined using the Lemeslow formula, with a sample af 149 respondents selected through accidental sampling. Primary data were collected dfrectly through questionnaires distributed ta patients visiting Puskesmas Sukaramai. Data analysis was carried out using both univariate and bivariate methods, With hypothesis testing conducted using the Chi-square statistical test. The study results indicate significant relationships between physical evidence (tangible) and patient satisfaction (p=0.000), reliability and patient satisfaction (p=0.000), responsiveness and patient satisfaction (p=0.000), assurance and patfent satisfaction (p=0.000), and empathy and patient satisfaction (p=0. 002 < 0.05. It is recommended that healthcare workers focus on improving service cleanliness, friendliness, and efficiency at Puskesmas Sukaramai to enhance patfent satisfaction.